2021
DOI: 10.4209/aaqr.200574
|View full text |Cite
|
Sign up to set email alerts
|

Effects of High-speed Wind, Humidity, and Temperature on the Generation of a SARS-CoV-2 Aerosol; a Novel Point of View

Abstract: The new coronavirus (SARS-CoV-2) is rapidly spreading across communities around the world.Respiratory droplet transmission is a common transmission route for many airborne diseases, including novel coronavirus disease . Wearing the face mask prevents respiratory droplet transmission. Both face mask leakage and non-use of the face mask under high-speed wind conditions can increase the risk of SARS-CoV-2 transmission. The respiratory droplets' behavior during sneezing or coughing (i.e., the size and the distance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
0
1
0
1
Order By: Relevance
“…However, prayer 3 received almost 0 particles due to the prayer location which is under the air-conditioner. This coincide with the finding from Nazari A. et al (2021), where the safest location from the viral infection is near the inlet. The airflow from the airconditioner is pushing the particles away from the prayer 3.…”
Section: Particle Depositionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, prayer 3 received almost 0 particles due to the prayer location which is under the air-conditioner. This coincide with the finding from Nazari A. et al (2021), where the safest location from the viral infection is near the inlet. The airflow from the airconditioner is pushing the particles away from the prayer 3.…”
Section: Particle Depositionsupporting
confidence: 90%
“…The spreading of respiratory viruses increases when a person sneeze near the fresh air ducts in the car park. 11 The author found that respiratory particle concentration in underground car parks depend on the jet fan air velocity and when more than one person exists in the car park, the transmission of viral particle will significantly increase. The coughing from manikin near the inlet have higher overall inhaled aerosol by other manikin positioned inside the room when compared to coughing from manikin positioned further from inlet.…”
mentioning
confidence: 99%
“…Data yang digunakan mengacu pada penelitian yang telah dilakukan oleh Aydin [4], Zhang [5] dan Nazari [6]. Aydin menyebutkan pada penelitiannya bahwa COVID-19 memiliki diameter rata-rata 100 nm dan jari-jari 5 × 10 −8 m. Menurut Zhang, rentang kecepatan droplet keluar dari mulut ketika bernapas, berbicara dan batuk berturut-turut yaitu 0,1 -1 m/s; 2 -10 m/s dan 10 -20 m/s.…”
Section: Metodologiunclassified
“…Under a high-speed wind situation, respiratory droplets may convert to very small respiratory droplets in the wind direction. In this situation, the risk of SARS-CoV-2 transmission increases (Nazari et al, 2021). One study stated that the humidity, wind speed, and sunlight have an indirect relationship with the outbreak rate (Ahmadi et al, 2020).…”
Section: Effects Of Meteorological Items and Covid-19 Outbreakmentioning
confidence: 99%